The Effectiveness Of Village-Owned Enterprises Policy In Percut Sei Tuan Subdistrict, Deli Serdang Regency - J.T. Hartoyo S. Nadeak; Tunggul Sihombing; Riant Nugroho (UNIVERSITAS PAKUAN, 2026)
This study aims to analyze the effectiveness of the Village-Owned Enterprise (VOE) policy in Percut Sei Tuan District, Deli Serdang Regency. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observation, and documentation and analyzed using the interactive model of Miles and Huberman. The analysis was guided by Nugroho’s policy effectiveness framework, covering policy accuracy, implementing actors, target accuracy, environmental support, and implementation process. The findings reveal that only four of the eighteen VOE operate effectively, while the remaining fourteen have not been able to sustain their institutional and business functions. The effectiveness of the active VOE is supported by the alignment of business activities with local potential, competent management, sound institutional governance, village government support, transparency, and community participation. Conversely, ineffective VOE are constrained by limited managerial capacity, weak governance, inadequate business feasibility, and low public participation. The study implies that strengthening managerial capacity, improving transparent financial governance, conducting business feasibility analysis, and enhancing participatory supervision are essential to improve the effectiveness and sustainability of VOE as instruments of rural economic development.